1997
DOI: 10.1128/jvi.71.2.1405-1416.1997
|View full text |Cite
|
Sign up to set email alerts
|

A novel cellular site-specific DNA-binding protein cooperates with the viral NS1 polypeptide to initiate parvovirus DNA replication

Abstract: Replication of linear single-stranded parvovirus DNA proceeds by a rolling-hairpin mechanism which generates long, palindromic, duplex concatamers. Processing to monomer length requires initiation from origins of DNA replication located at the 3 and 5 ends of each embedded monomer, reactions which can be recapitulated in vitro for minute virus of mice (MVM). To determine which cellular proteins were essential for replication from these origins, S100 extracts from 293S cells were fractionated on phosphocellulos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 36 publications
(38 reference statements)
1
65
0
Order By: Relevance
“…Proteins can be visualized as freely diffusing or interacting with nuclear chromosomes or protein compartments (Janicki and Spector, 2003;Bubulya and Spector, 2004). A number of nuclear replication proteins and APAR bodies have been shown to interact with NS1 (Christensen et al, 1997;Cziepluch et al, 2000;Bashir et al, 2001;Young et al, 2002a). However, the dynamics of this interaction has never been assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins can be visualized as freely diffusing or interacting with nuclear chromosomes or protein compartments (Janicki and Spector, 2003;Bubulya and Spector, 2004). A number of nuclear replication proteins and APAR bodies have been shown to interact with NS1 (Christensen et al, 1997;Cziepluch et al, 2000;Bashir et al, 2001;Young et al, 2002a). However, the dynamics of this interaction has never been assessed.…”
Section: Discussionmentioning
confidence: 99%
“…The sequence ACGTCAC has been shown to bind a variety of CREB/ATF family proteins present in cell extracts (Perros et al, 1995;Christensen et al, 1997a). However, the combinations of the 20 or so members of the ATF/CREB family of bZIP transcription factors potentially able to bind the MVM CRE as homodimers or heterodimers are legion.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant human placental CREB-327 protein was expressed from a baculovirus vector (Chen et al, 1991) and purified as reported previously (Christensen et al, 1997a). Selection experiments were performed, as described by Burnett et al (2001), using oligonucleotide P1, 5′-TGACAGTTCTGACCAAGGNNNCGNNNNNNNNNNNNNCCAGGTACCTATAGTTG Gf, where underlined sequences represent binding sites for forward Primer-1, 5′-TGACAGTTCTGACCAAGG-3′, and reverse Primer-2, 5′-CCAACTATAGGTACCTGG-3′, respectively.…”
Section: Degenerate Oligonucleotide Selection Analysis Of the Viral Crementioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, we may have purified away a factor that is not present in fraction IIA and that stimulates AAV DNA synthesis (see below). Recently, Christensen et al (8) identified a cellular factor called parvovirus initiation factor which was present in fraction I and required for nicking of the dimer bridge and initiation of DNA synthesis from the 3Ј origin in the related parvovirus minute virus of mice. Conceivably, this or a similar factor is needed for AAV as well.…”
Section: Discussionmentioning
confidence: 99%